2021
DOI: 10.1101/2021.12.20.473401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arsenal of Nanobodies for Broad-Spectrum Countermeasures against Current and Future SARS-CoV-2 Variants of Concerns

Abstract: Nanobodies offer several potential advantages over mAbs for the control of SARS-CoV-2. Their ability to access cryptic epitopes conserved across SARS-CoV-2 variants of concern (VoCs) and feasibility to engineer modular, multimeric designs, make these antibody fragments ideal candidates for developing broad-spectrum therapeutics against current and continually emerging SARS-CoV-2 VoCs. Here we describe a diverse collection of 37 anti-SARS-CoV-2 spike glycoprotein nanobodies extensively characterized as both mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…A panel of 37 anti-SARS-CoV-2 spike nanobodies was characterized as both monovalent and IgG Fc-fused bivalent modalities [ 102 ]. The analysis of binding characteristics showed that both monovalent and bivalent nanobodies have high affinity and high cross-reactivity against spike variants.…”
Section: Biophysical Characterization and Protein Engineering Of Sars...mentioning
confidence: 99%
See 1 more Smart Citation
“…A panel of 37 anti-SARS-CoV-2 spike nanobodies was characterized as both monovalent and IgG Fc-fused bivalent modalities [ 102 ]. The analysis of binding characteristics showed that both monovalent and bivalent nanobodies have high affinity and high cross-reactivity against spike variants.…”
Section: Biophysical Characterization and Protein Engineering Of Sars...mentioning
confidence: 99%
“…A total of 12 out of 20 tested bivalent nanobodies exhibited high efficacy in neutralizing the Delta variant. Of these nanobodies, nine were capable of neutralizing all tested variants [ 102 ] For the first time, this study demonstrated high epitope diversity, revealing that several NTD- and S2-specific nanobodies were potent and efficacious neutralizers in vitro and in vivo as well as remaining potent against the Alpha, Beta, Gamma, Delta, and Kappa variants [ 102 ]. Using computer-aided design, multi-specific VHH antibodies fused to human IgG1 Fc domains were constructed based on the epitope predictions for leading VHHs [ 103 ].…”
Section: Biophysical Characterization and Protein Engineering Of Sars...mentioning
confidence: 99%
“…In general, however, S2-specific monoclonal antibodies exhibit poor virus neutralizing activity. Single-domain antibodies (VHHs, also known as nanobodies) directed against the SARS-CoV-2 S2 subunit have also been reported, which, even as Fc-fusions, have low SARS-CoV-2-neutralizing activity (11, 12).…”
Section: Introductionmentioning
confidence: 99%